A proposed plan for implementing the public transport policy in the city of Ramadi / Anbar University as a model - Thameel, S.; Mahmood, Th.; Mustafa, A.; Mohson, A. (Anbar Journal of Engineering Sciences, 2021)
The development of cities in the infrastructure and urbanization and the increase in the population make people increase in the purchase of the private car, which in turn causes the congestion , pollution , accident and noise especially after 2003, as Iraq's import of cars increased to 5,800,000 cars distributed between the provinces, as 3Anbar province ranked ninth in the development number of cars with 174,000 cars according to the Central Bureau of Statistics of the Ministry of Planning. The university is the largest governmental institution that has the largest traffic volume of vehicles. We have three directions for entering the Anbar university they are east, middle and west directions. Total traffic volume from east, middle and west direction is 2165 vehicles which lead to traffic congestion in Ramadi city and Anbar university. The total traffic volume in private transportation in east, middle and west direction is 727,515 and 923 vehicles respectively. No of students in private transportation in east, middle and west direction is 4617, 3185 and3985 passengers respectively. As results of this research, there are three proposed parks one of them in the Sujaria at east direction, second park in Ramadi center at middle direction and third park in 5km area at west direction. In this paper, we make comparing between private and public transport in terms of fuel costs and time from the origin (the three proposed parks) to destination (Anbar University) assuming that private cars stopped in those three parks by using Park & Ride System and used buses with capacity of 40 passengers to transport students to the university. Depending on no. of passengers in private transportation from the three proposed parks to university we got the No. of buses from east park (Sujaria area), middle park (Ramadi center) and west park (7km area) to university which were 28, 20 and 25 bus respectively because each bus can transport four times.